Dinâmica de compostos orgânicos voláteis a partir de bioprocessos microalgais - Vieira, Karem Rodrigues (2021)
The metabolic versatility of microalgae provides solutions to technological challenges in the food industry. Issues that sound controversial, such as the removal of unpleasant odor from wastewater treatment plants, and the production of desirable aroma compounds is a possible hypothesis in processes using microalgae, but still little explored. In view of this, the objective of this research was to evaluate the dynamics of volatile organic compounds (VOCs) during experiments carried out with agro-industrial effluents, as well as the potential production of volatile compounds of commercial interest. The work was divided into two stages: In the first, the efficiency of microalgae-based systems in the deodorization of wastewater from meat processing and the bioconversion of these compounds into volatiles of industrial interest was evaluated. This step gave source to the article entitled: "The role of microalgae-based systems in the dynamics of the odors compounds in the meat processing industry”. This research showed the removal of 99.6% of unpleasant VOCs from wastewater in 72 hours of residence time, and concomitantly 15 volatile compounds were formed during the process. The second stage of the work was carried out in order to prove the efficiency of removing unpleasant compounds from wastewater through chromatographic olfactory analysis. The results generated a second article entitled: “The role of microalgae-based systems in the dynamics of odorous compounds in the meat processing industry. Part II - Olfactometry and sensory relevance”. The results showed that the compounds indole and skatol, which are the main odor markers in wastewater, did not present sensory perception after 72 hours of residence time, suggesting that they were completely removed. At the same time, a total of 11 compounds formed were perceptible and classified as fruity, citrus, green, and resinous by the judges. In addition, a review of microalgal VOCs was carried out, covering topics on microalgal volatile biosynthesis, factors that affect the formation of volatile compounds, application of volatile compounds, and VOC recovery techniques and published as a book chapter, entitled “Volatile organic compounds from microalgae”. Thus, it was concluded that microalgae-based systems are capable to mitigate the most unpleasant odors of wastewater from meat processing, in addition to generating a variety of volatile compounds of commercial interest, suggesting the possibility of exploring them for application in fine chemical or food industry.